COVID-19 Runs America: The Representation of Donald J. Trump in The Guardian News Article - Wijaya, Andreas Chrisanta; Tanto, Trisnowati (Master Program in Linguistics, Diponegoro University, 2023)
As COVID-19 globally spreads from one country to another, the commitment to resolve the crisis has ultimately fallen on world leaders. Consequently, recent public health and safety policies may become the target of controversies, in which people and media may question the government’s stance. This research examines Donald J. Trump’s representation in a newspaper article entitled “Coronavirus in America: Why the US Has Struggled to Tackle a Growing Crisis,” published by The Guardian in 2020. The article discusses Trump’s involvement in the issue of COVID-19 in the United States, in which the containment of the crisis has yet to be successful. The research employs Teun A. van Dijk’s Critical Discourse Analysis (CDA), emphasizing the three structural levels of news discourse: macrostructure, microstructure, and superstructure. Next, the qualitative descriptive research method is utilized, and the data are collected using library research. In terms of findings, it is found that the three structural aspects portray Trump in a negative light. It is hoped that the research can further contribute to CDA to COVID-19.